Adaptations to a semiaquatic lifestyle in the external ear of southern pinnipeds (Otariidae and Phocidae, Carnivora): Morphological evidences - Loza, Cleopatra Mara; Krmpotic, Cecilia Mariana; Galliari, Fernando Carlos; Andrés Laube, Pedro F.; Negrete, Javier; Scarano, Alejo Carlos; Loureiro, Julio; Carlini, Alfredo Armando; Barbeito, Claudio Gustavo (Zoology)
Pinnipeds are semiaquatic carnivorans that spend most of their lives in water and use coastal terrestrial, or ice pack, environments to breed, molt and rest. Certain characteristics of the ear have been linked to ecological aspects. In our contribution we focus on the study of the macroscopic and microscopic morphology of the external ear (with the exception of the osseous outer ear canal) of six species of Southern pinnipeds. In order to recognize the different components of tissues, sections were stained following several routine protocols. In addition, double-staining and enzymatic clearing (Alcian blue-alizarin red) was performed to assess the arrangement of skeletal elements in the OEC. The basic structure of the pinna in the southern otariids studied match those previously analyzed for Northern Hemisphere species. The cartilage macro anatomy of the OEC of Mirounga leonina and Arctocephallus gazella is different from that of the Northern Hemisphere species, with only one plate of cartilage, but markedly different between them. The histology of the otariids OEC is homogeneous along the entire extension, but phocids has three different regions (distal, middle, and proximal). The cartilage histology of most phocids is also different from that of analyzed otariids, with an elastic cartilage that resembles a myxoid-like tissue, but is not present in M. leonina, were the tissue around the OEC is very rich in adipocytes. The southern elephant seal M. leonina OEC has a combination of features similar to both the rest of the phocids and to the otariids. An auditory organ that is functional both over and under water could be essential for social behavior in these species. Fil: Loza, Cleopatra Mara. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de la Plata. Facultad de Cs.naturales y Museo. Laboratorio de Morfologia Evolutiva y Desarrollo.; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina ...